ANALISIS KEPUASAN PELANGGAN PENGGUNA LAYANAN ELECTRONIC CERTIFICATE OF ORIGIN PADA DIREKTORAT LALU LINTAS BARANG BADAN PENGUSAHAAN (BP) BATAM - Ari Ferdiansya; Bambang Hendrawan (Politeknik Negeri Batam, 2019)
This research attempts to measuring the degree of customer satisfaction in of Electronic Certificate of Origin at Batam goods traffic office through the quality of service Electronic Certificate of Origin website. The sampling technique used is purposive sampling. Total of sample are 196 respondents. Data were analyzed by using quantitative descriptive statistics. Data were analyzed by using quantitative descriptive statistics. Importance Pefomance Analysis (IPA) diagram shows that services item dimensions were spread among three a quadrant, That is 6 in a quadrant “main priority”, that is 7 in a quadrant “keep up the pace the performance of existing at the present time”. 5 other items was at quadrant “low priority”. And 3 item was at “Emphasis overblown” position.